2006
DOI: 10.1063/1.2213168
|View full text |Cite
|
Sign up to set email alerts
|

The defect structure, sintering behavior, and dielectric responses of Cr2O3-doped Sr0.5Ba0.5Nb2O6

Abstract: Phase structure, dielectric properties, and relaxor behavior of ( K 0.5 Na 0.5 ) NbO 3 -( Ba 0.5 Sr 0.5 ) TiO 3 lead-free solid solution for high temperature applications Effect of sintering temperature on the phase transition and dielectrical response in the relaxor-ferroelectricsystem 0.5PZN-0.5PZT Sr 0.5 Ba 0.5 Nb 2 O 6 ͑SBN50͒ with and without Cr 2 O 3 dopant had been prepared by the solid-state reaction. The structural variations of undoped and Cr 2 O 3 -doped SBN were examined by the x-ray diffractometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Tri or pentavalent cations are substituted at octahedral sites B1 and B2 [4] and C site (smallest interstice) is generally empty. Detailed literature survey reveals that a lot of work has been carried out on TB structure ferroelectric niobates in binary, ternary and quaternary systems [5][6][7][8][9][10][11][12]. Neurgaonkar et al [13] have reported the synthesis, structure and ferroelectric properties of M 6 2+ M 2 4+ Nb 8 O 30 where M 2+ = Ba, Sr or Ca and M 4+ = Ti, Sn or Zn.…”
Section: Introductionmentioning
confidence: 97%
“…Tri or pentavalent cations are substituted at octahedral sites B1 and B2 [4] and C site (smallest interstice) is generally empty. Detailed literature survey reveals that a lot of work has been carried out on TB structure ferroelectric niobates in binary, ternary and quaternary systems [5][6][7][8][9][10][11][12]. Neurgaonkar et al [13] have reported the synthesis, structure and ferroelectric properties of M 6 2+ M 2 4+ Nb 8 O 30 where M 2+ = Ba, Sr or Ca and M 4+ = Ti, Sn or Zn.…”
Section: Introductionmentioning
confidence: 97%
“…The defect reactions of undoped and Cr‐doped SBN50 had been determined via the study of the sintering behavior 34,35 . However, the conclusion drawn previously concerning the charge‐compensating defect of Ce‐doped SBN50 36 was misinterpreted and needs to be reassessed.…”
Section: Resultsmentioning
confidence: 99%
“…It clearly shows that the densification rate of SBN50 increases with the doping content for Ce dopant. Moreover, there are interesting results occurring in (Ce,Cr)‐doped SBN50: While the densification rate is not significantly changed with the doping content for the Ce/Cr ratio of 2, it is for Ce/Cr of 1, behaving like Cr‐doped SBN50 35 . Ce had been proved to be mainly in the valence state of 3+ 37 and suggested 38 to substitute Sr.…”
Section: Resultsmentioning
confidence: 99%
“…The TB structured compounds of a type (A 1 ) 5 (A 2 )(B 1 ) 3 (B 2 ) 7 O 30 and (A 1 ) 4 (A 2 ) 2 (B 1 ) 4 (B 2 ) 6 O 30 form a typical tetragonal filled tungsten-bronze structures whereas with formula (A 1 ) 2 (A 2 ) 4 C 4 (B 1 ) 2 (B 2 ) 8 O 30 belongs to fully filled tungsten-bronze structure. Detailed literature survey on TB structure compounds reveals that a lot of work has been carried out on structural and dielectric property of TB structure niobates and tantalates binary, ternary and quaternary systems [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Detailed studies of structural and electrical property especially impedance and conductivity of some members of this family is still lacking.…”
Section: Introductionmentioning
confidence: 99%